2010
DOI: 10.1029/2009gb003545
|View full text |Cite
|
Sign up to set email alerts
|

Constraint of the CO2 rise by new atmospheric carbon isotopic measurements during the last deglaciation

Abstract: [1] The causes of the ∼80 ppmv increase of atmospheric carbon dioxide (CO 2 ) during the last glacial-interglacial climatic transition remain debated. We analyzed the parallel evolution of CO 2 and its stable carbon isotopic ratio (d 13 CO 2 ) in the European Project for Ice Coring in Antarctica (EPICA) Dome C ice core to bring additional constraints. Agreeing well but largely improving the Taylor Dome ice core record of lower resolution, our d 13 CO 2 record is characterized by a W shape, with two negative d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
150
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(159 citation statements)
references
References 102 publications
(195 reference statements)
6
150
3
Order By: Relevance
“…This suggests that in the warmest areas of northern Italy temperatures never fell significantly below 10 • C during the summers of the LGM, since July air temperatures below 10 • C usually limit tree and forest growth (Lang, 1994). According to the Origlio record (Tinner et al, 1999), deglaciation in the southern Alpine foreland had started significantly before ∼ 18 000 cal yr BP, in line with increasing Northern Hemisphere summer insolation (Berger and Loutre, 1991) and increasing atmospheric CO 2 concentrations (Smith et al, 1999;Lourantou et al, 2010) (Fig. 6).…”
Section: Reconstructed Temperaturesmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests that in the warmest areas of northern Italy temperatures never fell significantly below 10 • C during the summers of the LGM, since July air temperatures below 10 • C usually limit tree and forest growth (Lang, 1994). According to the Origlio record (Tinner et al, 1999), deglaciation in the southern Alpine foreland had started significantly before ∼ 18 000 cal yr BP, in line with increasing Northern Hemisphere summer insolation (Berger and Loutre, 1991) and increasing atmospheric CO 2 concentrations (Smith et al, 1999;Lourantou et al, 2010) (Fig. 6).…”
Section: Reconstructed Temperaturesmentioning
confidence: 97%
“…However, a chronologically poorly constrained, though characteristic expansion of Betula nana, evidenced both by pollen and macrofossils, occurred at many sites north of the Alps prior to the Bølling-Allerød interstadial. This dwarf birch phase has been attributed either to pedogenesis or to an increase in summer temperatures (Ammann and Tobolski, 1983;Gaillard, 1985), but has also been interpreted as the result of increasing atmospheric CO 2 concentrations that started rising between ∼ 17 000 and ∼ 16 500 cal yr BP (Lourantou et al, 2010). On the basis of the available dates (some on terrestrial macrofossils) the expansion of the dwarf birch tundra has been dated to ∼ 17 500-15 000 cal yr BP (Welten, 1982;Ammann and Lotter, 1989).…”
Section: Reconstructed Temperaturesmentioning
confidence: 99%
“…Studies where discrepancies have been found between the expected and measured values when using BFI for extraction tests [Leuenberger et al, 1992;Lourantou et al, 2010] should consider the possibility that the BFI used may actually contain trace amounts of the gas being measured. [133] Although the CSIRO BFI ice performed best for CO 2 and ı 13 C of the BFIs used here, we still consider possible that a very small amount of gas is trapped in it.…”
Section: A6 Different Types Of Bfi Testedmentioning
confidence: 99%
“…For this analysis, we performed Monte-Carlo-style probabilistic assessments (n ¼ 10,000 simulations) based on the uncertainties associated with the various records. For CO 2 , CH 4 , and Antarctic temperature records (Monnin et al, 2001(Monnin et al, , 2004Loulergue et al, 2008;Lourantou et al, 2010;Stenni et al, 2010;Schmitt et al, 2012;Schneider et al, 2013;Landais et al, 2013;Parrenin et al, 2013;Ahn and Brook, 2014), we account for uncertainties associated with chronology (AICC 2012, Veres et al, 2013;Bazin et al, 2013) and proxy measurement in each record to determine the 68% (16 th e84th percentile) and 95% (2.5 th e97.5th percentile) probability intervals, the median (50 th percentile), and the probability maximum (modal value) with its 95% probability interval (e.g., Grant et al, 2012;Rohling et al, 2014;Marino et al, 2015). We probabilistically calculate greenhouse gas (GHG) components of Earth's radiative balance (DF CO2 , DF CH4 , and DF GHG ) from ice-core time series of CO 2 and/or CH 4 , referencing radiative forcing estimates to the values at AD1000 (cf.…”
Section: Implications For Concepts Of Glacial Inceptionmentioning
confidence: 99%